UTILIZATION OF BUSINESS INTELLIGENCE IN MARKETING STRATEGY FOR BALADO SHRIMP CRACKER PRODUCTS - Sudiantini, Dian; Bachri, Samsul; Alexander, Yanuar; Willson, Michael Aris; Bagasasi, Faizal (SENTRI: Jurnal Riset Ilmiah, 2024)
This research explores the integration of business intelligence (BI) tools in the marketing strategy for Balado Shrimp Cracker products, aiming to enhance consumer insights and competitive advantage in the snack industry. Through qualitative research methods, the study investigates how BI facilitates the identification and analysis of consumer preferences, purchasing behaviors, and competitor dynamics. The findings emphasize the importance of leveraging BI for data-driven decision-making, personalized marketing initiatives, and proactive market intelligence. By harnessing BI, Balado can optimize its marketing strategies, drive growth, and foster brand loyalty amidst a competitive landscape.